Case report: Isolated dissection of the left gastric artery: an unusual cause of acute abdominal pain - Frey, V.; Engelberger, R. P.; Psathas, E. (Frontiers in Cardiovascular Medicine, 2023)
Spontaneous and isolated dissection of the left gastric artery is a rare occurrence, with only a handful of cases reported in the medical literature. Clinical presentation may mimic more common intraabdominal pathologies; however, it is imperative to identify this condition promptly due to its potential serious consequences. This underscores the importance of maintaining a high level of clinical suspicion and including this pathology in the differential diagnosis of patients presenting with acute abdominal symptoms. Hence, this case report aims to increase awareness among clinicians about the importance of identifying and treating this rare condition promptly.A 69-year-old female experienced severe epigastric pain while attending a yoga class, prompting her admission to the emergency department 24 hours later due to the persistence of her symptoms. Following imaging work-up utilizing computed tomography angiography (CTA), she was diagnosed with a dissection of the left gastric artery. Notably, there was no associated aneurysm or any evidence of ischemia in the esophageal or gastric wall. Conservative management, including low-dose aspirin and blood pressure control, was implemented. After 6 months of follow-up, CTA demonstrated expansion of the true lumen and the absence of secondary aneurysm formation, leading to discontinuation of aspirin.The management of spontaneous dissection of visceral arteries is primarily determined by the presence of complications and organ ischemia. In the case of uncomplicated visceral artery dissections, first-line treatment comprises surveillance and antiaggregation. Nevertheless, the optimal duration of antiplatelet therapy and the necessity for long-term follow-up remain unclear. Endovascular or surgical interventions should be reserved for patients exhibiting deteriorating symptoms or complications, and the decision to pursue these interventions should be made on a caseby-case basis.